Peran Internet of Things dalam Transformasi Sistem Perpajakan di Era Digital - Yamin, Fawzyyah (Jurnal Ilmu Ekonomi dan Sosial (JIES), 2023)
This paper discusses the role of the Internet of Things (IoT) in the transformation of taxation systems in the digital era. The digital era, fueled by advancements in digital technology, brings significant innovations, including IoT, with substantial potential to optimize business processes and public services. IoT enables connectivity and real-time data exchange, reshaping the taxation paradigm from static to dynamic. Focusing on efficiency, accuracy, and transparency, this research identifies the impact of IoT implementation on taxation systems. Through case studies of Spain and Vietnam, it illustrates how IoT usage enhances tax administration efficiency and influences taxpayer compliance. Despite challenges and obstacles, the transformation of taxation systems in the digital era presents opportunities to improve tax revenue, transparency, and the relationship between tax authorities and taxpayers.